2013
DOI: 10.1002/jmv.23782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the shedding of three β‐herpesviruses in urine and saliva of children with renal disease

Abstract: Cytomegalovirus (CMV), human herpesvirus 6 (HHV-6) and 7 (HHV-7) are important pathogens in immunocompromised patients. To elucidate the kinetics of the three β-herpesviruses in saliva and urine samples were collected serially from children with renal diseases. Twenty children with renal diseases were enrolled in this study. A total of 240 saliva and urine samples were collected monthly from the patients over a 1-year period. Viral DNAs loads were measured by real-time PCR. In 10 CMV seropositive patients CMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
3
20
0
1
Order By: Relevance
“…Concerning the differences between children and adults, this study evidenced a higher prevalence of HHV-6 DNA in the saliva samples from children than from adults. This is in accordance with a recent study where HHV-6 was detected frequently in the saliva samples from children with renal disease [Yamamoto et al, 2013]. However, HHV-6 was detected in 58% of the saliva samples from children with malignancy by the use of a nested PCR [Lyall and Cubie, 1995].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Concerning the differences between children and adults, this study evidenced a higher prevalence of HHV-6 DNA in the saliva samples from children than from adults. This is in accordance with a recent study where HHV-6 was detected frequently in the saliva samples from children with renal disease [Yamamoto et al, 2013]. However, HHV-6 was detected in 58% of the saliva samples from children with malignancy by the use of a nested PCR [Lyall and Cubie, 1995].…”
Section: Discussionsupporting
confidence: 93%
“…The results observed for HIV-infected patients and multiple sclerosis patients were lower with 38% of detection [Gautheret-Dejean et al, 1997] and similar, with 65% of detection, respectively [Höllsberg et al, 2005]. HHV-6 median load (11,950 copies/ml) was higher than that observed for healthy subjects (5,000 and 1,917 copies/ ml) [Cone et al, 1993;Miller et al, 2005] and was similar to that found in children with renal disease [Yamamoto et al, 2013].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Using qPCR, viral DN A kinetics can be evaluated and compared for symptomatic and asymptomatic infected turtles, helping to predict disease outbreaks, explain differences in disease states, and improve transmission risk management (e.g. Yamamoto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Upper respiratory infections, such as the influenza virus and human bocavirus HboV-1, a mild respiratory disease, can be detected in the saliva up to 1 year after primary infection (87, 88). In addition, cytomegalovirus (CMV), Epstein–Barr virus, human herpes virus (HHV) 6, and HHV7 can all be detected in human saliva (8991). CMV, the most common cause of congenital hearing loss in children in developed countries (92), was one of the first viruses to be successfully detected through salivary analysis in the newborn (93).…”
Section: Salivary “Omics”mentioning
confidence: 99%